CONTRADICTIONS OF THE WORLD SYSTEM IN THE NEAREST FUTURE An interview with PIOTR DUTKIEWICZ, Professor of Political Science at Carleton University (Ottawa, Canada) - Dutkiewicz, P.; Arusyak, H.L. (RUDN Journal of Political Science, 2018)
Piotr Dutkiewicz is the professor of Political Science and the co-director of the Center for Governance and Public Policy at Carleton University (Ottawa, Canada). He got his education at Warsaw University and the Russian Academy of Sciences. He was a Visiting Fellow at St. Peter’s and Nuffield Colleges in Oxford and a Visiting Professor at Berkeley University, Institute for International Relations. He is a member of the Valdai Club, a group of forty renowned experts on Russia. In 2009, he received the Order of Friendship of the Russian Federation from President Dmitry Medvedev. In this interview professor Dutkiewicz will tell us about the main contradictions shaping the new world order.